Faktor Kondisi Lingkungan Rumah Sebagai Determinan Kejadian Penyakit Tuberkolosis Paru Di Wilayah Puskesmas Pampang - Husniar; Muhammad Ikhtiar; Ulfa Sulaeman (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Tuberculosis is an infectious disease caused by the mycobacterium tuberculosis bacteria that enter the body with symptoms of coughing that will last for 2 weeks, which will be followed by various additional symptoms, namely phlegm mixed with blood, coughing up blood, shortness of breath, and weakness, decreased appetite, weight loss, sweating at night without physical activity and fever for one month. The study aimed to determine whether there was a relationship between ventilation, natural lighting, residential density, and household contact with people with Pulmonary Tuberculosis. This type of research is observational analytic with a cross-sectional study approach. This study was conducted in the working area of ​​the Pampang Health Center, Makassar City. The research time was carried out in June-July 2024. This study's population were residents suspected of tuberculosis who had been temporarily treated and registered in the TB register book at the Pampang Health Center in January-December 2023—a total of 160. Moreover, the number of participants in this study was 114. Using the Slovin Formula. Data presentation in this study was carried out in the form of a distribution table and narrative or explanation of the description of the variables. The study's results showed a relationship between ventilation, lighting, residential density, household contact, and pulmonary tuberculosis incidence. It is hoped that further research will be conducted on other factors that can explain the causes of pulmonary tuberculosis.